Online shopping in the opinion of young consumers = Zakupy w Internecie w opinii młodych konsumentów - Barska, Anetta (Zielona Góra: Faculty of Economics and Management Press)
Analysis of the statistical data indicates that 52% of people in Poland use the Internet on a regular basis - at least once a week - and the greatest activity is displayed by young people at the age of 16-24 years - 91% of the whole. The income from e-commerce clearly increases year by year and its further dynamic growth is expected. The Internet contributed to changes in spending behavior of the consumers. The knowledge of them may play a very important role in developing e-strategy which might help to build up lasting competitive advantage. In the following study the author presents the results of her own survey concerning purchasing behaviors of young consumers and presents their possible implications.
Keywords: handel elektroniczny; młody konsument; internet; e-strategia; e-commerse; young consumer; e-strategy